2021
DOI: 10.1038/s41598-021-86438-1
|View full text |Cite
|
Sign up to set email alerts
|

Blood donor variability is a modulatory factor for P. falciparum invasion phenotyping assays

Abstract: Human erythrocytes are indispensable for Plasmodium falciparum development. Unlike other eukaryotic cells, there is no existing erythroid cell line capable of supporting long-term P. falciparum in vitro experiments. Consequently, invasion phenotyping experiments rely on erythrocytes of different individuals. However, the contribution of the erythrocytes variation in influencing invasion rates remains unknown, which represents a challenge for conducting large-scale comparative studies. Here, we used erythrocyte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…We used 1 mg/mL of chymotrypsin in the present study based on previous knowledge that higher concentrations yielded similar levels of efficiency. Moreover, we recently showed that the efficiency of enzyme treatment could be influenced by erythrocytes' surface receptor densities (31). Notwithstanding, the current observation about Rh2b, together with previous data, highlight the contributory role of Rh2b to erythrocyte invasion and its likely involvement in dictating phenotypic variation.…”
Section: B Asupporting
confidence: 50%
“…We used 1 mg/mL of chymotrypsin in the present study based on previous knowledge that higher concentrations yielded similar levels of efficiency. Moreover, we recently showed that the efficiency of enzyme treatment could be influenced by erythrocytes' surface receptor densities (31). Notwithstanding, the current observation about Rh2b, together with previous data, highlight the contributory role of Rh2b to erythrocyte invasion and its likely involvement in dictating phenotypic variation.…”
Section: B Asupporting
confidence: 50%
“…Samples used in this study were collected from Ghanaian children with uncomplicated malaria visiting the LEKMA hospital in Accra. To monitor the in vitro growth patterns of freshly collected P. falciparum clinical isolates, parasites were initially allowed to grow in the patient-derived erythrocytes for a minimum period of 96 hours after which freshly washed O + erythrocytes (from a single donor) ( Thiam et al., 2021 ) were added and growth tests were performed for isolates that successfully grew. Of the 25 isolates used in this study, 19 (76%) yielded detectable parasitemia 48 hours following in vitro adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Target erythrocytes were treated with either 250 mU/mL of neuraminidase, 1 mg/mL of trypsin or 1 mg/mL of chymotrypsin for 1 hour at 37° C with gentle shaking and washed thrice with RPMI1640 medium. The efficiency of enzyme treatment was assessed as previously described ( Thiam et al., 2021 ). Treated erythrocytes were then labelled with 20 µM of carboxyfluorescein diacetate, succinimidyl ester (CFDA-SE) (Thermo Fisher Scientific) for two hours at 37° C with gentle shaking and protected from light exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Target erythrocytes were treated with either 250 mU/mL of neuraminidase, 1 mg/mL of trypsin or 1 mg/mL of chymotrypsin for 1 hour at 37º C with gentle shaking and washed thrice with RPMI1640 medium. The efficiency of enzyme treatment was assessed as previously described 18 . Treated erythrocytes were then labelled with 20 µM of carboxyfluorescein diacetate, succinimidyl ester (CFDA-SE) (Thermo Fisher Scientific) for two hours at 37º C with gentle shaking and protected from light exposure.…”
Section: Enzyme Treatment and Erythrocyte Invasion Phenotyping Assaysmentioning
confidence: 99%
“…Samples used in this study were collected from Ghanaian children with uncomplicated malaria visiting the LEKMA hospital in Accra. To monitor the in vitro growth patterns of freshly collected P. falciparum clinical isolates, parasites were initially allowed to grow in the patient-derived erythrocytes for a minimum period of 96 hours after which freshly washed O + erythrocytes (from a single donor) 18 were added and growth tests were performed for isolates that successfully grew. Of the 25 isolates used in this study, 19 (76%) yielded detectable parasitemia 48 hours following in vitro adaptation.…”
Section: P Falciparum Clinical Isolates Show Different Growth Patterns During Early In Vitro Culture Adaptationmentioning
confidence: 99%